Conceptual design of cryogenic system for comprehensive research facility for key fusion reactor core systems. (April 2019) - Hu, L; Zhang, Q; Zhu, Z; Lu, X; Zhou, Z; Fu, B; Cheng, A
Abstract: To break the bottlenecks of key components of fusion reactors, the Chinese government have included the construction of a Comprehensive Research Facility for Key Fusion Core System in its recent National Grand Project plans. It encompasses two synergistic research platforms, one for superconductor and magnets capable of a maximum field of 15T, and the other for divertor physics, material and component capable of a maximum plasma particle flux of 10 24 /m 2 s. The cryogenic system provides the 4.5K, 3K and 1.8K cooling power to all the magnets, superconductor components and cryopumps. The total average cooling capacity is 7.2kW/4.5K (1kW/3K, 250W/1.8K). This paper describes the conceptual design of the system including the helium refrigerators and cryogenic research platform. The features of the cryogenic system and the project schedule are also described.